1973
DOI: 10.1073/pnas.70.3.747
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ascorbic Acid on Hepatotoxicity Caused by Sodium Nitrite Plus Aminopyrine

Abstract: The oral treatment of rats with sodium ascorbate in combination with sodium nitrite and aminopyrine prevents the rise in serum alanine aminotransferase (EC 2.6.1.2) observed when nitrite and aminopyrine are given alone. Ascorbic acid also affords protection, whereas dehydroascorbic acid exerts no protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…When significant differences by ANOVA were detected analysis of a difference between the means of the treated and control groups were performed by using Dunnett's test. The percent protection was calculated according to the equation described by Kamm et al, 1973: 100-100 (D 1/ D 2 ) Where D 1 is the mean for the protected group-the mean for the controls and D 2 is the mean for the hepatotoxic group-the mean for the controls.…”
Section: Discussionmentioning
confidence: 99%
“…When significant differences by ANOVA were detected analysis of a difference between the means of the treated and control groups were performed by using Dunnett's test. The percent protection was calculated according to the equation described by Kamm et al, 1973: 100-100 (D 1/ D 2 ) Where D 1 is the mean for the protected group-the mean for the controls and D 2 is the mean for the hepatotoxic group-the mean for the controls.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when AsA was given with NaNO 2 and AP, the inhibitory effect was less potent than that of HTHQ. It was reported that AsA and sodium ascorbate (NaAsA) protected rats against liver tumor production or hepatotoxicity by simultaneous treatment with NaNO 2 and secondary amines such as AP 3,22) or morpholine. 23) AsA has been shown to inhibit the genotoxicity of nitrosoamines derived from NaNO 2 and secondary amines such as morpholine or proline in the Comet assay, 24) and is suggested to inhibit nitrosamine formation by reducing nitrous anhydride to nitric oxide, a non-nitrosating species, in the absence of catalysts.…”
Section: Discussionmentioning
confidence: 99%
“…Even the latter possibility is sometimes worth considering. For example, it has been suggested that vitamin C may prevent the formation of carcinogenic nitrosamines by reacting with nitrite within the stomach (12,13).…”
Section: Vitamin C -General Observationsmentioning
confidence: 99%